Low-Temperature Synthesis of YVO4:Bi3+, Eu3+ Nanoparticle Phosphors Using a Methanol Solution of Trivalent Cations. (1st January 2016) - Ohno, Takayuki; Iso, Yoshiki; Isobe, Tetsuhiko
Abstract : A homogeneous solution of Y 3+, Bi 3+, and Eu 3+ in methanol was used for low-temperature (70°C) synthesis of YVO4 :Bi 3+, Eu 3+ nanoparticles. X-ray diffraction and fluorescence analyses revealed phase-pure tetragonal YVO4 :Bi 3+, Eu 3+ . Transparent colloidal solutions were prepared having well-dispersed ∼8-nm YVO4 :Bi 3+, Eu 3+ nanoparticles. Increases in elemental Bi content at the constant Eu content increased the lattice spacing linearly. This reveals that Bi 3+, which is larger than Y 3+ and Eu 3+, substitutionally incorporated in YVO4 :Eu 3+ . The absorption edges and photoluminescence excitation edges were red-shifted by doping Bi 3+ in YVO4 :Eu 3+, and red emission from Eu 3+ was observed under near-ultraviolet excitation. These results indicate that Bi 3+ and Eu 3+ were successfully co-doped into the YVO4 host crystal. Concentration quenching was not observed with increasing Bi-doping even until 6.5 at%, although the quenching of bulk YVO4 :Bi 3+, Eu 3+ prepared by solid-state reaction was observed with >3 at% in a previous report. This implies a better chemical homogeneity of Bi in the host crystal or a structural disorder which prevents the energy migration between Bi 3+ .